Different bacterial cargo in apoptotic cells drive distinct macrophage phenotypes - Salina, Ana Carolina Guerta [UNESP]; de Aquino Penteado, Letícia [UNESP]; Dejani, Naiara Naiana; Silva-Pereira, Ludmilla [UNESP]; Raimundo, Breno Vilas Boas [UNESP]; Corrêa, Gabriel Ferranti [UNESP]; Oliveira, Karen Cristina [UNESP]; Ramalho, Leandra Naira Zambelli; Boko, Mèdéton Mahoussi Michaël; Bonato, Vânia L. D.; Henrique Serezani, C.; Medeiros, Alexandra Ivo [UNESP] (Springer Nature, 2024)
The removal of dead cells (efferocytosis) contributes to the resolution of the infection and preservation of the tissue. Depending on the environment milieu, macrophages may show inflammatory (M1) or anti-inflammatory (M2) phenotypes. Inflammatory leukocytes are recruited during infection, followed by the accumulation of infected and non-infected apoptotic cells (AC). Efferocytosis of non-infected AC promotes TGF-β, IL-10, and PGE2 production and the polarization of anti-inflammatory macrophages. These M2 macrophages acquire an efficient ability to remove apoptotic cells that are involved in tissue repair and resolution of inflammation. On the other hand, the impact of efferocytosis of infected apoptotic cells on macrophage activation profile remains unknown. Here, we are showing that the efferocytosis of gram-positive Streptococcus pneumoniae-AC (Sp-AC) or gram-negative Klebsiella pneumoniae-AC (Kp-AC) promotes distinct gene expression and cytokine signature in macrophages. Whereas the efferocytosis of Kp-AC triggered a predominant M1 phenotype in vitro and in vivo, the efferocytosis of Sp-AC promoted a mixed M1/M2 activation in vitro and in vivo in a model of allergic asthma. Together, these findings suggest that the nature of the pathogen and antigen load into AC may have different impacts on inducing macrophage polarization.
Keywords: Efferocytosis; Infected apoptotic cells; Lung inflammation; Macrophages